Pengaruh Dukungan Organisasi dan Self Efficacy terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening pada PT Yasiga Sarana Utama Padang - Sari Raudatusyifa; Marta Widian Sari; Selvi Zola Fenia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of organizational support and self efficacy on employee performance with organizational commitment at PT Yasiga Sarana Utama Padang. The method used is quantitative. The study used primary data (questionnaires) from 333 respondents of PT Yasiga Sarana Utama Padang employees. The method used is Structural Equation Modeling Analysis with Partial Least Square (PLS) 3.0. The results of this study indicate that (1) organizational support has a positive and significant effect on organizational commitment. (2) organizational support has a positive and significant effect on employee performance. (3) self efficacy has a positive and significant effect on organizational commitment. (4) self efficacy has a positive and significant effect on employee performance. (5) organizational commitment has a positive and significant effect on employee performance. (6) organizational commitment significantly mediates organizational support on employee performance (7) organizational commitment cannot mediate self efficacy on employee performance. Some of the results of this study contradict theory and previous research, because of the different phenomena and objects studied.